Thermomechanical study and thermal behavior of plasticized poly(Lactic acid) nanocomposites (SCOPUS) - Zorah Mohammed (Tanjung Malim, 2021)
Thermomechanical study and thermal behavior of plasticized poly(Lactic acid) nanocomposites (SCOPUS) by Zorah Mohammed